Tailoring the topological surface state in ultrathin α -Sn(111) films - Rogalev, VA; Reis, F; Adler, F; Bauernfeind, M; Erhardt, J; Kowalewski, A; Scholz, MR; Dudy, L; Duffy, LB; Hesjedal, T; Hoesch, M; Bihlmayer, G; et al. (American Physical Society, 2019)
We report on the electronic structure of α -Sn films in the very low thickness regime grown on InSb(111)A. High-resolution low photon energy angle-resolved photoemission spectroscopy allows for the direct observation of the linearly dispersing two-dimensional (2D) topological surface state (TSS) that exists between the second valence band and the conduction band. The Dirac point of this TSS was found to be 200 meV below the Fermi level in 10-nm-thick films, which enables the observation of the hybridization gap opening at the Dirac point of the TSS for thinner films. The crossover to a quasi-2D electronic structure is accompanied by a full gap opening at the Brillouin-zone center, in agreement with our density functional theory calculations. We further identify the thickness regime of α -Sn films where the hybridization gap in the TSS coexists with the topologically nontrivial electronic structure and one can expect the presence of a one-dimensional helical edge state.